Transforming Healthcare with Artificial Intelligence in Pakistan: A Comprehensive Overview - Laraib Umer; Muhammad Hashim Khan; Yasar Ayaz (Pakistan Armed Forces Medical Journal, 2023)
Artificial Intelligence (AI) is transforming healthcare globally, including in Pakistan. This research journal paper provides an overview of the role and significance of AI in healthcare, ethical considerations, regulatory frameworks, challenges faced by AI healthcare startups, and the current landscape of AI adoption in Pakistan's healthcare system. AI has the potential to revolutionize disease prevention, diagnosis, and treatment by leveraging large healthcare datasets, advanced computational power, and machine learning algorithms. It improves patient outcomes, enhances clinical decision-making, and optimizes healthcare delivery. Globally, AI applications in healthcare encompass medical imaging, clinical decision support, drug discovery, genomics, and remote patient monitoring. AI algorithms accurately diagnose various medical conditions, predict treatment responses, and identify therapeutic targets. Successful AI implementations include combating antimicrobial resistance and improving pediatric healthcare. Ethical considerations in AI healthcare involve bias mitigation, privacy, transparency, and the role of healthcare professionals in shared decision-making. Regulatory frameworks and guidelines are being developed worldwide to ensure safe and responsible AI implementation. Quality criteria for AI-based prediction models focus on performance, interpretability, generalizability, and robustness. Legal and ethical considerations encompass liability, accountability, and the principles of beneficence, autonomy, and justice. In Pakistan, the integration of AI in healthcare can address challenges like limited resources and uneven distribution of healthcare facilities. AI technologies can analyze medical data, diagnose disease outcomes, and personalize treatment plans.